Concordance of tumour characteristics and survival clustering among pairs of first-degree relatives with breast cancer - Elisabetta Rapiti; Jean-Christophe Tille; Evelyne Fournier; Essia Saiji; Dominique Weintraub; Hanifa Bouzourene; Valeria Viassolo; Christine Bouchardy; Pierre O. Chappuis; Simone Benhamou (Swiss Medical Weekly, 2020)
BACKGROUND